GROWTH PATTERN, REPRODUCTIVE PERFORMANCE AND SEASONAL SENSITIVITY OF BOVAN NERA AND ISA BROWN PARENT-STOCK CHICKENS IN IBADAN NIGERIA (2011)
Parent stocks (PS) of exotic hybrids have contributed immensely to commercial poultry production in Nigeria. Their continued optimal utilization depends on their performance test. Information on performance indices of PS layer breeds in South-West Nigeria is however limited. The growth, reproductive performance and seasonal sensitivity of Bovan Nera (BN) and Isa Brown (IB) hybrids were evaluated. Secondary data on 24 batches of PS of each of BN and IB kept over a period of 10 years (1999-2008) in Ajanla Farms, Ibadan were used. Average batch population was 3896 pullets and 600 cockerels at point-of-lay. Records on Body Weight (BW), Age, Hen-Day-Production (HDP), Egg Weight (EWt), Egg fertility (EF), Egg Hatchability (EH), Pullet Day-Old Chicks produced (PDOC) and Hatching Rejects (HR) in four seasons: Early-Wet (EW, April-July); Late-Wet (LW, August-October); Early-Dry (ED, November-January) and Late-Dry (LD, February-March) were obtained. Data were standardized and analysed for growth, Age-at-first-egg (AFE), HDP characteristics, reproduction, seasonal sensitivity, genotype-season interaction using descriptive statistics, ANOVA, correlation and regression (p=0.05).There was no significant difference in BW (g) and growth rate (g/day) between hybrids: 1724.8±562.8 and 1549.8±543.3; 1.4±2.3 and 1.1±1.6 for BN and IB hens, respectively. Effect of seasons on AFE was not significant in both hybrids, but ED and LD seasons delayed AFE. The HDP values (%) recorded for BN (63.2) and IB (72.9) in ED were significantly higher than in other seasons. There were significant differences in EF (80.8 and 88.7%), EH (69.1 and 73.6%), PDOC (32.6 and 36.1%) and EWt (56.2 and 59.9 g) for BN and IB respectively in EW season. EF (86.2 and 89.5%) and EH (73.1 and 73.9%) in LW were highest within hybrids respectively. Phenotypic correlation (r) between Age and Hen Weight, Age and EWt, Hen Weight and EWt, EF and EH, EF and PDOC, and EH and PDOC were 0.78, 0.74, 0.68, 0.73, 0.72 and 0.98 in BN; and 0.77, 0.52, 0.53, 0.69, 0.71, and 0.97 in IB respectively. The positive and significant correlation between HR and EWt (r = 0.14 and 0.13), for BN and IB respectively, indicated increase in HR as EWt increased. The environmental performance in body weight of both hybrids was significantly depressed before 10 weeks in cocks and throughout the life cycle of hens, except at 10 to 16 weeks in the BN hen. Performance depression was also observed in HDP (-10.2%), EF (-6.9%) and EH (-14.4%) in IB, and EWt (-2.9 and -3.2%) in both genotypes respectively over their life-time period. Predictions of BW by Age (R2 = 0.85, 0.84), EWt by Age-in-production (R2 = 0.65, 0.65), and PDOC by EH (R2 = 0.99, 0.95) in both hybrids were significant at 25-75 weeks. Hen day production, egg fertility, egg hatchability, pullet day-old chicks were higher in Isa Brown than Bovan Nera during the early-dry season. Body weight was higher in the cocks of both hybrids in early-dry and late-dry than in early-wet and late-wet seasons. The sensitivity of Isa Brown was lower than Bovan Nera except in hen weight